PENGARUH EXPERIENTIAL MARKETING TERHADAP REPURCHASE INTENTION MELALUI CUSTOMER SATISFACTION (Survei pada Konsumen Warung Selat Mbak Lies di Surakarta) - Ashifa Dila Maharani; Marjam Desma Rahadhini; Retno Susanti (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
The purpose of this research is to analyse 1) the effect of experiential marketing on repurchase intention; 2) the influence of experiential marketing on customer satisfaction; 3) the effect of customer satisfaction on repurchase intention; 4) the effect of experiential marketing on repurchase intention through customer satisfaction. This research is conducted at Warung Selat Mbak Lies Surakarta. The sampling technique uses purposive sampling with 160 respondents. The types of data that used are qualitative data and quantitative data, data sources consist of primary data and secondary data. Data analysis techniques used are the test instrument and Structural Equation Modeling (SEM). The results show that experiential marketing influences repurchase intention. Experiential marketing affects customer satisfaction. Customer satisfaction affects repurchase intention. Experiential marketing has an effect on repurchase intention through customer satisfaction at Warung Selat Mbak in Surakarta.